Social activity of the youth: Approaches to the assessment of forms, motives and factors in the contemporary Russian society - I V Trotsuk; K G Sokhadze (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
Despite the fact that the social activity of young people has become actual and popular topic of the official and scientific discourses, the methodological aspects of its sociological study still do not attract the necessary research attention. The authors note the popularization of the subject in the sociologically relevant way in the mid-1960s and in the first part of the article summarize the conceptual and categorical apparatus for its study, in particular, the diversity of approaches to the definition of the ‘social activity’, its motives (socially significant needs primarily), subjective ‘dimension’, structural levels, types of goals (substantive, procedural, pragmatic and altruistic, collective or personal, etc.) as well as its actual forms (personal, group, institutional, and others) and internal and external factors of its development. The authors focus on the practical theory of reframing proposed by C. Clement and consider through it the results of national surveys conducted in Russia in recent years to assess the interpretations and the scope of the social activity of Russians in general and the youth in particular. Thus, the data show the minor involvement of citizens in social activities and its mainly declarative nature. The most important form of the youth social activity nowadays is the participation in the non-profit organizations, especially public unions, that is why the authors conclude the overview of the features and manifestations of the social activity of young people in the contemporary Russian society with the description of the types and functions of public associations, the basic analytical approaches to their study and the assessment of the true extent of their current activity.